MODELO TERMOENERGÉTICO CALIBRADO DO RESTAURANTE ESTUDANTIL DO CEFETMG CAMPUS II - Duarte, Matheus de Andrade; Freitas, Ludmylla Faria de; Lima, Frederico Romagnoli Silveira; Oliveira, Raquel Diniz (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The sustainable use of electricity is a global challenge. In this scenario, building thermal studies can improve the indoor human thermal conditions as well as minimize the HVAC consumption of electricity. The authors aimed at developing a calibrated model of a school restaurant that will foster human thermal comfort and building energy efficiency studies. To this intent, the research dealt with the restaurant data beyond its architectural design such as schedules, building systems and indoor temperatures, among others. Two Onset HOBO Data Logger measured the temperature in situ. Therefore, a case study model was created by using Energy Plus version 8.7.0. The simulated temperatures were compared with those gathered by measurement. A similar behavior could be notice on the results, at many period of the year, indicating that the model is calibrated. Further simulations by using this model could foster the building thermal behavior prediction and drive to building enhances.